2011
DOI: 10.5402/2011/949686
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label Pilot Study to Assess the Efficacy and Safety of Virgin Coconut Oil in Reducing Visceral Adiposity

Abstract: Introduction. This is an open-label pilot study on four weeks of virgin coconut oil (VCO) to investigate its efficacy in weight reduction and its safety of use in 20 obese but healthy Malay volunteers. Methodology. Efficacy was assessed by measuring weight and associated anthropometric parameters and lipid profile one week before and one week after VCO intake. Safety was assessed by comparing organ function tests one week before and one week after intake of VCO. Paired t-test was used to analyse any difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
3
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 18 publications
1
46
3
18
Order By: Relevance
“…This shows that VCO supplementation causes a decrease in body weight. Previous studies in humans have shown that VCO appears to promote a reduction in abdominal obesity [23, 24]. According to a study conducted by St-Onge [25], medium-chain fatty acids (MCFA), compared to long-chain fatty acids, increase energy expenditure and resulted in faster satiety.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that VCO supplementation causes a decrease in body weight. Previous studies in humans have shown that VCO appears to promote a reduction in abdominal obesity [23, 24]. According to a study conducted by St-Onge [25], medium-chain fatty acids (MCFA), compared to long-chain fatty acids, increase energy expenditure and resulted in faster satiety.…”
Section: Discussionmentioning
confidence: 99%
“…This fruit is a fi brous drupe that consists of a thin hard skin called exocarp, a thicker layer of fi brous mesocarp, the hard endocarp, the white endosperm called kernel, and a large cavity fi lled with liquid (Chan and Elevitch 2006). The oil is obtained of coconut kernel and it is a natural functional food rich in medium-chain triglycerides (MCTs), mainly the saturated fatty acids with approximately 50% of the lauric acid (Liau et al 2011). The lauric acid has potential virucidal and bactericidal actions (Lieberman et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Os peróxidos são os primeiros compostos formados quando um óleo ou gordura deteriora (produtos primários da oxidação). (23) Logo, o índice de peróxidos é um método que apresenta maior aplicabilidade se utilizado para avaliar estágios iniciais da deterioração, quando os peróxidos atingem um pico e depois declinam. A partir de então, tem-se o aumento das concentrações dos produtos secundários da oxidação, como o malondialdeído (MDA).…”
Section: Discussionunclassified